2018
DOI: 10.1080/14992027.2018.1470337
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal sound localisation accuracy in individuals with conductive hearing loss: effect of the bone conduction implant

Abstract: Individuals with mixed/conductive hearing loss may benefit from a unilateral BCI in sound localisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The results from the ongoing clinical study have shown so far improved performance in basic tone and speech audiometry tests (Eeg-Olofsson et al 2014;Reinfeldt, Håkansson, Taghavi, Freden Jansson, et al 2015). The effect of the BCI during more complex tasks is currently under investigation, with focus on sound localisation in the study by Asp and Reinfeldt (2018), and on speech recognition in a multitalker cocktail party scenario in the current study.…”
Section: Introductionmentioning
confidence: 88%
“…The results from the ongoing clinical study have shown so far improved performance in basic tone and speech audiometry tests (Eeg-Olofsson et al 2014;Reinfeldt, Håkansson, Taghavi, Freden Jansson, et al 2015). The effect of the BCI during more complex tasks is currently under investigation, with focus on sound localisation in the study by Asp and Reinfeldt (2018), and on speech recognition in a multitalker cocktail party scenario in the current study.…”
Section: Introductionmentioning
confidence: 88%
“…These stimuli had long-term frequency spectra similar to the unmodulated noise used with the Hagerman Sentences, and thus similar to the spectrum of a female voice ( Hagerman 1982 ). One of these two stimuli was a musical melody ( Asp & Reinfeldt 2018 , 2020 ; Johansson et al 2019 ; Eklöf et al 2020 ) that minimized monaural level cues by naturally occurring amplitude modulations. The other broadband stimulus was a stationary noise, thus increasing the availability of monaural level cues compared with the musical melody.…”
Section: Methodsmentioning
confidence: 99%
“…The perceived auditory azimuth was defined as the median of the final 10 gaze/AoI intersection samples obtained during the 1.6-sec sound-only period, that is, a 500-msec sampling period. Sound localization accuracy was quantified by an error index (EI; Gardner & Gardner 1973;Asp et al 2011;Asp & Reinfeldt 2018) which was calculated as follows: where P is the set of loudspeakers (1 to 12), i = the presented loudspeaker (1 to 12), k = the perceived loudspeaker (1 to 12), and n = 12 (the number of loudspeakers). The EI ranged from 0 (perfect performance) to 1 (random performance).…”
Section: Test Proceduresmentioning
confidence: 99%
“…Presentation order was randomized and children either verbally indicated the perceived sounding loudspeaker (which was labeled) or by pointing at it. Sound localization was quantified by an Error Index (Gardner & Gardner 1973 ; Asp & Reinfeldt 2018 ) ranging from 0 (perfect performance) to 1 (random performance).…”
Section: Methodsmentioning
confidence: 99%
“…Presentation order was randomized and children either verbally indicated the perceived sounding loudspeaker (which was labeled) or by pointing at it. Sound localization was quantified by an Error Index (Gardner & Gardner 1973;Asp & Reinfeldt 2018) ranging from 0 (perfect performance) to 1 (random performance). Spoken Language Abilities • Expressive vocabulary and naming ability were examined with the 60-item Boston Naming Test (BNT) in all children older than 4 years (Kaplan et al,Reference Note 3).…”
Section: Hearing and Listening Abilitymentioning
confidence: 99%